This preview has intentionally blurred sections. Sign up to view the full version.
View Full DocumentThis preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: 8 Techniques of Integration Over the next few sections we examine some techniques that are frequently successful when seeking antiderivatives of functions. Sometimes this is a simple problem, since it will be apparent that the function you wish to integrate is a derivative in some straightforward way. For example, faced with integraldisplay x 10 dx we realize immediately that the derivative of x 11 will supply an x 10 : ( x 11 ) ′ = 11 x 10 . We don’t want the “11”, but constants are easy to alter, because differentiation “ignores” them in certain circumstances, so d dx 1 11 x 11 = 1 11 11 x 10 = x 10 . From our knowledge of derivatives, we can immediately write down a number of an tiderivatives. Here is a list of those most often used: integraldisplay x n dx = x n +1 n + 1 + C, if n negationslash = − 1 integraldisplay x − 1 dx = ln  x  + C integraldisplay e x dx = e x + C integraldisplay sin x dx = − cos x + C 149 150 Chapter 8 Techniques of Integration integraldisplay cos x dx = sin x + C integraldisplay sec 2 x dx = tan x + C integraldisplay sec x tan x dx = sec x + C integraldisplay 1 1 + x 2 dx = arctan x + C integraldisplay 1 √ 1 − x 2 dx = arcsin x + C 8Ùb ×Ø iØÙØ iÓÒ Needless to say, most problems we encounter will not be so simple. Here’s a slightly more complicated example: find integraldisplay 2 x cos( x 2 ) dx. This is not a “simple” derivative, but a little thought reveals that it must have come from an application of the chain rule. Multiplied on the “outside” is 2 x , which is the derivative of the “inside” function x 2 . Checking: d dx sin( x 2 ) = cos( x 2 ) d dx x 2 = 2 x cos( x 2 ) , so integraldisplay 2 x cos( x 2 ) dx = sin( x 2 ) + C. Even when the chain rule has “produced” a certain derivative, it is not always easy to see. Consider this problem: integraldisplay x 3 radicalbig 1 − x 2 dx. There are two factors in this expression, x 3 and radicalbig 1 − x 2 , but it is not apparent that the chain rule is involved. Some clever rearrangement reveals that it is: integraldisplay x 3 radicalbig 1 − x 2 dx = integraldisplay ( − 2 x ) parenleftbigg − 1 2 parenrightbigg (1 − (1 − x 2 )) radicalbig 1 − x 2 dx. This looks messy, but we do now have something that looks like the result of the chain rule: the function 1 − x 2 has been substituted into − (1 / 2)(1 − x ) √ x , and the derivative 8.1 Substitution 151 of 1 − x 2 , − 2 x , multiplied on the outside. If we can find a function F ( x ) whose derivative is − (1 / 2)(1 − x ) √ x we’ll be done, since then d dx F (1 − x 2 ) = − 2 xF ′ (1 − x 2 ) = ( − 2 x ) parenleftbigg − 1 2 parenrightbigg (1 − (1 − x 2 )) radicalbig 1 − x 2 = x 3 radicalbig 1 − x 2 But this isn’t hard: integraldisplay − 1 2 (1 − x ) √ x dx = integraldisplay − 1 2 ( x 1 / 2 − x 3 / 2 ) dx (8 . 1) = − 1 2 parenleftbigg 2 3 x 3 / 2 − 2 5 x 5 / 2 parenrightbigg + C = parenleftbigg 1 5 x − 1 3 parenrightbigg...
View
Full Document
 Fall '11
 GUICHARD
 Antiderivatives, Derivative, Rational function

Click to edit the document details